Inhibiting Wnt/beta‐catenin in CTNNB1‐mutated endometrial cancer. Issue 8 (26th May 2021) - Moroney, Marisa R.; Woodruff, Elizabeth; Qamar, Lubna; Bradford, Andrew P.; Wolsky, Rebecca; Bitler, Benjamin G.; Corr, Bradley R.
Abstract: The role of β‐catenin/TCF transcriptional activity in endometrial cancer (EC) recurrence is not well understood. We assessed the impact of Wnt/β‐catenin inhibition in EC models. In an analysis of the Cancer Genome Atlas, we confirmed that CTNNB1 mutations are enriched in recurrent low‐risk EC and showed that aberrant Wnt/β‐catenin pathway activation is associated with recurrence. We studied CTNNB1 ‐wildtype (HEC1B, Ishikawa) and CTNNB1 ‐mutant (HEC108, HEC265, HEC1B‐S33Y, Ishikawa‐S33Y) EC cell lines. Dose response curves were determined for 5 Wnt/β‐catenin pathway inhibitors (Wnt‐C59, XAV‐939, PyrPam, PRI‐724, SM04690). XAV939, Wnt‐C59 and PyrPam inhibited function upstream of β‐catenin transcriptional activity and were ineffective at inhibiting cell viability. In contrast, PRI724 and SM04690 indirectly inhibited β‐catenin transcriptional activity and significantly reduced cell viability in CTNNB1 ‐mutant cell lines. Treatment with SM04690 reduced cell viability (Licor Cell stain) in all EC cell lines, but viability was significantly lower in CTNNB1 ‐mutant cell lines ( p  < 0.01). Mechanistically, SM04690 significantly inhibited proliferation measured via 5′‐bromo‐2′‐deoxyuridine incorporation and reduced T cell factor (TCF) transcriptional activity. HEC1B, HEC1B‐S33Y and HEC265 tumor‐bearing mice were treated with vehicle or SM04690. Tumors treated with SM04690 had smaller mean volumes than those treated with vehicle ( p  < 0.001, p  = 0.014, p  = 0.06). In HEC1B‐S33Y and HEC265 tumors, SM04690 treatment significantly reduced Ki67 H‐scores compared to vehicle ( p  = 0.035, p  = 0.024). Targeting the Wnt/β‐catenin pathway in CTNNB1 ‐mutant EC effectively inhibited proliferation and β‐catenin/TCF transcriptional activity and blunted tumor progression in in vivo models. These studies suggest β‐catenin transcriptional inhibitors are effective in EC and particularly in CTNNB1 ‐mutant EC, highlighting a potential therapeutic vulnerability for treatment of CTNNB1 ‐mutant EC.